Identification of multiple abiotic stress tolerant donors for climate-resilient rice (Oryza sativa) development - CHAKRABORTY, KOUSHIK; ROY, SOMNATH; JENA, P; DASH, G K; BARIK, M; BEHERA, MOTILAL; SAR, P; SENAPATY, J; BAIG, M J; SWAIN, PADMINI (The Indian Journal of Agricultural Sciences, 2023)
The increasing occurrence of adverse weather events is continuously challenging agricultural production globally. The wide genetic base of rice (Oryza sativa L.) and the availability of a diverse set of germplasm can be explored to identify multiple abiotic stress-tolerant donors for rice improvement. Therefore, an experiment was conducted during 2018–21 at ICAR-National Rice Research Institute, Cuttack, Odisha to evaluate diverse rice germplasm (68 accessions) for vegetative stage drought and submergence stress and for their anaerobic germination potential. Under drought stress, 49 accessions showed a drought score (DS) of 1 indicating a tolerance response. The early vegetative score indicated that 58 accessions were highly vigorous, while the drought recovery score indicates that >90% of the genotypes showed good recovery after the drought cycle. The same genotypes showed a average survival rate (SR) of 48% under two weeks of complete submergence. Among them, 11 were found highly tolerant with >70% SR and 26 genotypes scored positive SUB1A locus by SNP-based functional marker AEX1. Nearly 50% of the genotypes scored positive for SUB1A, based on both AEX1 and Sub1A203 markers, which nearly matched the phenotyping result. Out of 68, only 4 accessions showed more than 50% germination under anaerobic conditions. A multivariate analysis showed that 11 genotypes had both drought and submergence tolerance, while 6 genotypes were having tolerance to drought and anaerobic germination. We found only 1 accession (IC516149) tolerant to all these 3 stresses which can be identified as a potential donor for multiple abiotic stresses.